"I Just Feel Like I Always Did": Inotropic Dependency at End of Life. (July 2020) - Latimer, Abigail; Pope, Natalie D.; McFarlin, Jessica M.
Background: Patients not considered for mechanical circulatory support or heart transplant may be dependent on inotropic therapy at end of life. End-of-life conversations in advanced heart failure can be challenging for providers, but guidelines recommend frequent goals-of-care conversations when inotropes are used as a palliative treatment. The purpose of this study was to identify aspects of care pertinent for health-care professionals working with patients in end-stage heart failure who are receiving continuous inotropic support. Methods: Qualitative analysis was used to examine 3 audio-recorded semistructured interviews with 1 patient, her family, and her cardiologist. The selected patient was an older adult, diagnosed with advanced heart failure, and dependent on continuous inotropic therapy with no other advanced treatment options available. Results: The analysis revealed that (1) reliance on others, (2) contending with uncertainty, and (3) deciding when to discontinue inotropic support were identified as themes central to the patient's and provider's experience. Conclusion: This study offers insight into how to best support and communicate with patients having advanced heart failure who are dependent on continuous inotropic therapy at end of life.